Etiological study of superficial radial nerve neuropathy: series of 34 patients - Shields, Lisa B. E.; Iyer, Vasudeva G.; Zhang, Yi Ping; Shields, Christopher B. (Frontiers in Neurology, 2023)
Objectives Superficial radial nerve (SRN) neuropathy is a rare focal neuropathy leading to pain and paresthesia of the dorsolateral aspect of the hand. Reported causes include trauma, extrinsic compression, or it may be idiopathic. We describe the clinical and electrodiagnostic (EDX) features of 34 patients with SRN neuropathy of varied etiology. Methods This is a retrospective study of patients with upper limb neuropathy referred for EDX studies who were found to have SRN neuropathy based on clinical and EDX findings. Twelve patients also had ultrasound (US) evaluations. Results Decreased pinprick sensation was noted in the distribution of the SRN in 31 (91%) patients, and a positive Tinel’s sign was observed in 9 (26%). Sensory nerve action potentials (SNAPs) were not recordable in 11 (32%) patients. Of the patients who had a recordable SNAP, the latency was delayed, and the amplitude was decreased in all cases. Of the 12 patients who underwent US studies, 6 (50%) had an increased cross-sectional area of the SRN at or immediately proximal to the site of injury/compression. A cyst was located adjacent to the SRN in 2 patients. The most common cause of SRN neuropathy was trauma in 19 (56%) patients, of which 15 were iatrogenic. A compressive etiology was identified in 6 patients (18%). No specific etiology was detected in 10 patients (29%). Conclusion This study is aimed at raising the awareness among surgeons about the clinical features and varied causes of SRN neuropathy; such knowledge may potentially lessen iatrogenic causes of injury.